Field and farm-level data on agricultural land use for the European Union - Clemens Jänicke; Kristoffer Ansbak Petersen; Phillip Schmidts; Daniel Müller; Martin Rudbeck Jepsen (Scientific Data)
Abstract We present field-level land-use data from the Integrated Administration and Control System (IACS), featuring extended thematic details on farm-level indicators and organic cultivation. The data cover 19 of 27 EU member states, with annual time series that extend up to 17 years in some member states. The IACS data are invaluable for analysing land-use changes and farm-level characteristics with fine spatial, thematic, and temporal details. We provide an overview of the data sources, outline the pre-processing and harmonisation workflow and provide maps that exemplify the coverage and potential analyses. The data inventory constitutes a living document to which we will add additional data should these become available.